STRUKTUR KOMUNITAS LAMUN DI PULAU SAPUDI KABUPATEN SUMENEP - Hidayatullah Hasana; Wahyu Andy Nugraha (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTSeagrass is the only higher plant that can live in waters with high salinity. This plant has true roots, stems, leaves. Sapudi Island is an island that is rich in marine biota, which live in seagrass or that only feed on seagrass, so it is necessary to know the structure of the seagrass community. This study aims to determine the type, density, cover, community structure and substrate of seagrass in Sapudi Island, Sumenep Regency. Sampling was carried out by using the transect squared plot measuring 1x1 m in size with a plot inside measuring 20x20 cm. Data is taken at 4 stations according to the cardinal directions and at each station 3 points are taken and each point there are 10 transects by carrying out transects along 100 m parallel to the coastline. The results showed that the types of seagrass found were Enhalus acoroides, Thalassia hemprichii, Syringodium isoetifolium and Halophila ovalis. The highest value of density and cover of seagrass is at station 1 and the lowest value is at station 4. The highest frequency occurs at station 1 with a total number of 2.067 and the lowest value is at station 4 with a total amount of 0.8. The value of diversity at stations 1, 2 and 3 was medium, while at station 4 was low. The uniformity values at stations 1, 2, 3 and 4 are in the stable category. And the domination values at stations 1, 2, 3 and 4 are in the non-domination category. The highest Importance Value Index results in Enhalus acoroides seagrass ranged from 158 to 250 and the lowest was in Halophila ovalis from 6,989 - 27.30. The results of the relationship between seagrass density and sediment are said to have a weak variable relationship with a value of 0.006 (0.6%)Keywords: Community Structure, Seagrass, Sapudi IslandABSTRAKLamun adalah satu satunya tumbuhan tingkat tinggi yang dapat hidup di perairan dengan salinitas tinggi. Tumbuhan ini memiliki akar, batang, daun yang sejati. Pulau Sapudi merupakan pulau yang kaya akan biota laut yang bertempat tinggal di lamun atau yang hanya sekedar mencari makan di lamun, sehingga perlu untuk mengetahui struktur komunitas lamun. Penelitian ini bertujuan untuk mengetahui jenis, kepadatan, penutupan, struktur komunitas dan substrat lamun yang ada di Pulau Sapudi Kabupaten Sumenep. Pengambilan sampel dilakukan dengan metode transek kuadrat petak yang berukuran 1x1 m dengan petak didalamnya berukuran 20x20 cm. Data diambil di 4 stasiun sesuai dengan arah mata angin dan di setiap stasiun di ambil 3 titik dan setiap titik ada 10 transek dengan melakukan trasnsek sepanjang 100 m yang sejajar dengan garis pantai. Hasil menunjukkan bahwa jenis lamun yang ditemukan Enhalus acoroides, Thalassia hemprichii, Syringodium isoetifolium dan Halophila ovalis. Nilai kepadatan dan penutupan lamun tertinggi pada stasiun 1 dan nilai terendah pada stasiun 4. Frekuensi tertinggi terjadi pada stasiun 1 dengan jumlah total 2,067 dan nilai terendah pada stasiun 4 dengan jumlah total 0,8. Nilai keanekaragaman pada stasiun 1, 2 dan 3 kategori sedang, sedangkan pada stasiun 4 kategori rendah. Nilai keseragaman pada stasiun 1, 2, 3 dan 4 kategori stabil. Dan nilai dominasi pada stasiun 1, 2, 3 dan 4 masuk kategori tidak dominasi. Hasil Indeks Nilai Penting tertinggi pada jenis lamun Enhalus acoroides berkisar 158 – 250 dan terendah pada lamun Halophila ovalis 6,989 – 27,30. Hasil hubungan kepadatan lamun dan sedimen dikatakan mempunyai hubungan variable lemah dengan nilai 0,006 (0,6%) Kata kunci: Struktur Komunitas, Lamun, Pulau Sapudi